Energy-Efficient Technologies Are Saving a Vital Industry in Bangladesh - Taif Ul Islam, Muhammad; Gopal, Rajeev; Hossain, Mustahid (World Bank, Washington, DC, 2012)
The Bangladesh foundry industry is a crucial element of the country's light engineering sector, but it suffers from reliance on outdated technologies, inefficient production processes, and an inability to diversify products. This smart lesson describes the challenges and lessons learned from International Finance Corporation's (IFC's) efforts to revitalize the industry in the Bogra region by introducing new technologies.